2021
DOI: 10.3389/fimmu.2021.707217
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype-Specific Expression Analysis of MHC Class II Genes in Healthy Individuals and Rheumatoid Arthritis Patients

Abstract: HLA-DRB1 alleles have been associated with several autoimmune diseases. For anti-citrullinated protein antibody positive rheumatoid arthritis (RA), HLA-DRB1 shared epitope (SE) alleles are the major genetic risk factors. In order to study the genetic regulation of major histocompatibility complex (MHC) Class II gene expression in immune cells, we investigated transcriptomic profiles of a variety of immune cells from healthy individuals carrying different HLA-DRB1 alleles. Sequencing libraries from peripheral b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Early data had shown that major histocompatibility complex (MHC) was associated with the risk of RA ( 51 ). This risk effect was related to differences in protein structure and expression ( 52 ). SARS-CoV-2 infection was found to cause downregulation of major histocompatibility complex class I (MHC-I) in vivo and in vitro ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early data had shown that major histocompatibility complex (MHC) was associated with the risk of RA ( 51 ). This risk effect was related to differences in protein structure and expression ( 52 ). SARS-CoV-2 infection was found to cause downregulation of major histocompatibility complex class I (MHC-I) in vivo and in vitro ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…How may HLA variants affect T-cell fate? The mechanism could depend for example on characteristics of the peptide repertoires presented in the different MHC II variants 25 , 67 69 , by differential interactions between the TCR and the HLA that may affect peptide recognition 70 or by different cell type specific expression levels of the MHC II depending on the HLA variant 71 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that when compared to the standard single reference mapping, AltHapAlignR improved the accuracy of HLA expression quantification. Recently, AlthHapAlignR was applied in a study demonstrating allele-specific expression in HLA-DRB1 in patients with rheumatoid arthritis and in healthy controls ( 72 ).…”
Section: Methods In Hla Expression Quantificationmentioning
confidence: 99%
“…However, in many cases further studies are needed to confirm whether the expression alone is the predisposing factor and how the regulatory variation affects differential expression in diseases. Elevated HLA expression levels have been associated with inflammatory bowel diseases ( 56 , 76 ), scleroderma patients with interstitial lung disease ( 77 ), ankylosing spondylitis ( 78 ), Graves’ disease ( 79 ), systemic lupus erythematosus ( 80 ), rheumatoid arthritis ( 72 ), and multiple sclerosis ( 81 ). Additionally, in celiac disease and type 1 diabetes, higher expression of DQA1*05 and DQB1*02 alleles was found in patients when compared to healthy controls ( 82 , 83 ).…”
Section: Hla Expression In Human Diseasesmentioning
confidence: 99%